Russia-Ukraine War and the Global Crisis: Cross-Country Impact Analysis on Poverty and Food Security - Diao, Xinshen; Dorosh, Paul A.; Thurlow, James (International Food Policy Research Institute, 2022)
Presented by Xinshen Diao, Paul Dorosh, and James Thurlow, all with the International Food Policy Research Institute, Washington DC. This is part of the Global Crisis Country Series.